SPSS from A to Z : - Sprinthall, Richard C. (Pearson/A and B, 2009)
This brief SPSS manual covers virtually everything a first year statistics student will ever have to face! It includes all the necessary tests, as well as some addistional sophisticated tests for those students in advanced statistics or research methods courses.